PENGARUH KEHADIRAN OJEK ONLINE TERHADAP KEPUASAN PELANGGAN ONLINE DAN DAYA SERAP PENGANGGURAN DI MASYARAKAT BANYUMAS - Widodo Wibisono; Muhammad Hidayatulah Holili (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
The presence of ojek-online in Banyumas Regency turned out to be able to provide satisfaction for its customers, especially in Banyumas Regency. many as ojek-online in the Banyumas Regency and surrounding areas so that very many unemployed and already working residents are now working as ojek-online because in addition to the benefits achieved, it also has its own charm. Although it has received criticism from both the government and conventional ojek, slowly the existence of ojek-online can now be received positively by the wider community in Indonesia, especially in Banyumas Regency, because in addition to the easy ordering method, it also saves time, costs and energy. The presence of ojek-online turns out to be very helpful for public transportation, especially in certain rural areas where no transportation is available or transportation is available but time is limited, so the presence of ojek-online brings fresh air and bright hope in increasing population mobility in remote areas that are difficult and expensive to transport.